Perfil dos pacientes internados em UTI não covid: antes e durante a pandemia do coronavírus - Mauricio, Caren Caroline Rubira [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
At the end of 2019, the disease caused by the SARS-CoV-2 virus - known as covid-19 - spread around the world. Transmitted by inhalation or direct contact with contaminated droplets, covid-19 is part of a family that causes respiratory infections, which can progress to Severe Acute Respiratory Syndrome (SRAG). Due to the seriousness of the disease and the higher number of admissions to Intensive Care Units (ICUs), many hospitals reached their maximum capacity, requiring the suspension of admissions and elective procedures. In order to prevent the spread of the disease, and better serve patients who needed ICU for other reasons during the covid-19 pandemic, some institutions organized themselves and separated the beds of contaminated patients from uncontaminated patients, called non-contaminated ICUs. covid. Objective: To identify the profile of patients admitted to a non-covid ICU and correlate it with the workload of nursing professionals before and during the covid19 pandemic. Method: This is a cross-sectional study, with a quantitative approach, with data collection from management reports provided by the institution's information technology service. Data refer s to the months of March 2019 to February 2020 and March 2020 to February 2021. The study variables were age, sex, diagnosis, length of stay and outcome of patients admitted to the non-covid ICU; and workload of the nursing team through the Nursing Activities Score (NAS) of a highly complex University Hospital in the interior of the State of São Paulo. All non-covid adult ICU patients with a minimum stay of 24 hours during the research period were included. Results: It was evident that the profile related to age, sex and length of stay did not show any significant difference during the two periods. Regarding diagnoses, a significant increase in the number of hospitalized patients with cardiovascular problems was evidenced. As for the workload, there was a significant reduction during the pandemic, and a greater number of NAS observations in the same period. The workload of patients who evolved to death was greater; in addition to a significant increase in the workload, the longer the length of stay during the pandemic. Conclusion: There was no significant difference in the profile of patients admitted to a non-covid ICU during the pandemic, regarding gender and age. Significant increase in the number of cardiovascular disease diagnoses during the pandemic. The number of NAS observations was also statistically significant during the pandemic, being proportional to the increase in workload. The other variables were not related to the workload of the nursing team.

No fim de 2019, se espalhou pelo mundo a doença causada pelo vírus SARS-CoV-2 – denominada covid-19. Transmitida por inalação ou contato direto com gotículas contaminadas, a covid-19 faz parte de uma família causadora de infecções respiratórias, que podem evoluir para a Síndrome Respiratória Aguda Grave (SRAG). Frente à gravidade da doença e ao maior número de internação em Unidades de Terapia Intensiva (UTIs), muitos hospitais atingiram sua capacidade máxima, sendo necessária a suspensão de internações e procedimentos eletivos. Com o objetivo de evitar a proliferação da doença, e melhor atender os pacientes que necessitaram de UTI por outras causas durante a pandemia de covid-19, algumas instituições se organizaram e separaram os leitos de pacientes contaminados de pacientes não contaminados, denominadas UTI não covid. Objetivo: Identificar o perfil dos pacientes admitidos em UTI não covid e correlacionar com a carga de trabalho dos profissionais de enfermagem antes e durante a pandemia de covid-19. Método: Trata-se de um estudo transversal, de abordagem quantitativa, com coleta de dados a partir de relatórios gerenciais fornecidos pelo serviço de informática da instituição. Os dados são referentes aos meses de março de 2019 a fevereiro de 2020 e março de 2020 a fevereiro de 2021. As variáveis do estudo foram idade, sexo, diagnóstico, tempo de internação e desfecho dos pacientes admitidos na UTI não covid; e carga de trabalho da equipe de enfermagem por meio do Nursing Activities Score (NAS), de um Hospital Universitário de alta complexidade do interior do Estado de São Paulo. Foram incluídos todos os pacientes internados na UTI adulto não covid, com permanência mínima de 24 horas no período da pesquisa. Resultados: Evidenciou-se que o perfil relacionado a idade, sexo e tempo de internação não apresentou diferença significativa durante os dois períodos. Com relação aos diagnósticos, foi evidenciado um aumento significativo no número de pacientes internados com problemas cardiovasculares. Quanto à carga de trabalho, observou-se uma redução significativa durante a pandemia e um maior número de observações do NAS no mesmo período. Sendo maior a carga de trabalho com pacientes que evoluíram à óbito, além de um aumento significativo da carga de trabalho quanto maior o tempo de internação durante a pandemia. Conclusão: Não houve diferença significativa do perfil dos pacientes admitidos em UTI não covid, durante a pandemia, quando a sexo e idade. Houve um aumento significativo do número de diagnósticos de doenças cardiovasculares durante a pandemia. O número de observações do NAS também se mostrou estatisticamente significativo durante a pandemia, sendo proporcional ao aumento da carga de trabalho. As demais variáveis não apresentaram relação com a carga de trabalho da equipe de enfermagem.
Comparation of characteristics of a intensive care unit - before ans during coronavirus pandemic
Keywords: Workload; Intensive care units; Covid 19 pandemic; Nursing; Carga de trabalho; Unidades de terapia intensiva; Covid-19; Enfermagem